Draft Annual Plan 2004-2005 Volume-II Sector: Industries and Minerals Andaman and Nicobar Administration - Planning Commission (Planning Commission, 2004)
Capital is one of the important resources without it no industry can be established. In order to provide the capital for establishment of SSI/Tiny Handicrafts units in this remote and industrially backward territory of Andaman & Nicobar Islands Administration has been providing soft term loans facilities to the entrepreneurs/ unemployed youths for establishment / expansion / modernization of self employment ventures through various developmental programmes under the scheme Financial Assistance to Entrepreneurs.
Andaman and Nicobar Administration, Planning Department